Answer: (x^2+5x+6)/(x-2)
This is one single fraction. The stuff up top is x^2+5x+6. The stuff down below is x-2
============================================
Work Shown:
We multiply out the expressions (x+3) and (x+2) as they are both in the numerator. If you want, you can think of (x+2) as (x+2)/1
Multiplying (x+3) and (x+2) gives us this
(x+3)(x+2) = x(x+2) + 3(x+2) ... see note below
(x+3)(x+2) = x^2+2x + 3x + 6
(x+3)(x+2) = x^2 + 5x + 6
This is the stuff that will be on top in the final answer. The denominator x-2 stays the same.
note: I used the distribution property (a+b)(c+d) = a(c+d)+b(c+d)